(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Ischemic heart disease (IHD) is one of the leading causes of mortality in Pakistan. With advancement in research, multiple causes have contributed in development of web of causation of this public health issue. The objective of this study was to assess gender differences in risk factors associated with ischemic heart disease in patients presenting at the biggest cardiology hospital of Lahore. Patients and methods: A comparative cross-sectional study was carried out in Punjab Institute of Cardiology, Lahore from January to August, 2018 on a sample of 296 diagnosed patients of IHD, through non-probability consecutive sampling technique. Data was collected on pretested questionnaire. The data was analyzed using SPSS version 22. Chi-Square test of significance was applied and a p-value ≤0.05 was considered statistically significant. Results: The mean age of participants was 45±12 years with predominance of male patients (71.3%). Frequency of risk factors for IHD included increase body mass index (83.8%), hypertension (61%), insufficient physical activity (43%), diabetes (38.5%) and smoking (23%). Increase serum cholesterol was reported in 95% and triglycerides in 99% of the participants. Gender difference was significant with females residing in urban population (p=0.054) and exercise routine (p=0.034). Males showed high tendency of IHD with smoking pattern (p<0.001) contrary to presence of diabetes in females (p=0.05), hypertension (p=0.054), BMI (p=0.0379) and stressful event in life (p=0.002). Males showed regular intake of medicines (p =0.045) after diagnosis as compared to female population. Conclusion: There is more frequency of ischemic heart disease in males as compared to females. Significant association was observed with residence in urban area, presence of diabetes, hypertension, high BMI and stressful event in life in occurrence of ischemic heart disease in female population.